Cyclodextrin Films with Fast Solvent Transport and Shape‐Selective Permeability. Issue 26 (24th April 2017) - Villalobos, Luis Francisco; Huang, Tiefan; Peinemann, Klaus‐Viktor
Abstract : This study describes the molecular‐level design of a new type of filtration membrane made of crosslinked cyclodextrins—inexpensive macrocycles of glucose, shaped like hollow truncated cones. The channel‐like cavities of cyclodextrins spawn numerous paths of defined aperture in the separation layer that can effectively discriminate between molecules. The transport of molecules through these membranes is highly shape‐sensitive. In addition, the presence of hydrophobic (cavity) and hydrophilic (ester‐crosslinked outer part) domains in these films results in high permeances for both polar and nonpolar solvents. Abstract : A filtration membrane made of crosslinked cyclodextrins is reported. The channel‐like cavities of cyclodextrins spawn numerous paths of defined aperture in the separation layer that can effectively discriminate between molecules. The transport of molecules through these membranes is highly shape‐sensitive. In addition, the presence of hydrophobic (cavity) and hydrophilic (ester‐crosslinked outer part) domains in these films results in high permeances for both polar and nonpolar solvents.